A clean dispersant for nano-silica to enhance the performance of cement mortars. (15th October 2022) - Qian, Xin; Wang, Jialai; Wang, Liang; Fang, Yi; Chen, Peiyuan; Li, Mengxiao
Abstract: Nanoparticles can be used to enhance the performance of concretes. However, dispersants (surfactants) are commonly needed to overcome the aggregation/agglomeration of nanoparticles. Existing dispersants are mainly petroleum-based products. Their manufacturing and incorporation into concretes can have a harmful impact on the environment. To address this issue, this study proposes using an edible, plant-based product, tannic acid (TA), as a clean dispersant for colloidal nano-silica (CNS) in concretes. This can be done by simply mixing CNS particles with a TA solution. The produced CNS suspension can then be used as the mixing water to make cement mortars. Experimental studies suggest that a layer of TA is coated onto the silica nanoparticle, producing a TA-SiO2 biohybrid nanoparticle. Particle distribution analysis shows that this TA layer on the CNS is around 4.35 nm. The TA coating not only prevents the aggregation/agglomeration of nanoparticles but also delays the pozzolanic reaction between the nano-silica and calcium hydroxide (CH) in the concrete, making them available for filling nanopores in the hydrated cement paste. As a result, the microstructure of the produced cement paste is densified, as confirmed by mercury intrusion porosimetry, scanning electron microscopy, and nanoindentation testing. Particularly, capillary pores smaller than 50 nm are significantly reduced by the new biohybrid nanoparticles. This leads to 37% improvement in the compressive strength at 28d of the cement mortar with the TA dispersed CNS over that of the mortar made without using TA to disperse CNS.